High Sugar Concentration Inhibits TOR Signaling Pathway in Arabidopsis thaliana - Pereyra, Cintia; Parola, Rodrigo; Lando, Ana Paula; Rodriguez, Marianela; Martínez Noël, Giselle María Astrid (Springer, 2023)
Sugars are not only energy sources, but also central molecular signals that regulate growth, development, and response to environmental stresses. It is well recognized that sugars activate TOR kinase, the key integrator of energy availability that connects external and internal signals to regulate growth in eukaryotes. However, the specific effect of different types of sugars and their concentrations on TOR signaling has not been studied in detail. Thus, we studied the activation of the root apical meristem (RAM), which is a TOR-dependent process, and TOR activity in vivo in seedlings of Arabidopsis thaliana treated with different types and concentrations of sugars. The results show that exogenous sucrose (Suc), glucose (Glc), and fructose (in a minor extent), induced RAM reactivation and TOR activity; however, at high concentration, Glc did not induce the RAM nor the kinase activity. In contrast, trehalose was not able to affect RAM length or activate TOR. High concentration of sugars, which resemble some stress conditions, inhibited TOR activity.